Exploring the Purchasing Motives of Young Pakistani Consumers for Foreign Brands - Rafi, Arslan; ., Sharjeel Saqib; ., Ali Iftikhar Choudhary; ., Syed Azeem Akhtar (Information Management and Business Review, 2012)
Cross-border service relationships are considerable issues in Pakistan, which tend researchers to work in this area of research. The core purpose of this study was to explore the impact of quality, satisfaction, and value on purchase intentions for foreign brands among young Pakistani customers. The data was collected from a random sample of 500 university students through questionnaire designed by the researchers. The findings suggest that providing quality and satisfaction to Pakistani ethnocentric customers does not guarantee the brand to earn loyalty in return. Foreign brands can succeed in creating brand value through creating a convinced link with some tangible benefits and by creating means of self-presentation for the customers. The student’s responses can be assumed as a limitation of this study, which can be justified by considering the fact that the study is first of its type in the Pakistani environment.